Impact Of Fly Ash-Amended Vermicompost And Fertilizer On Soil Microbial Density And Enzymatic Activities Under Semi-Arid Conditions Of Bundelkhand (India) (Applied Biological Research, 2022)
Enormous quantities of hazardous coal fly ash (FA), generated by thermal  power plants, adversely affect the soil and water quality. The present field  experiment, conducted under semi-arid conditions of Bundelkhand (India)  in 2018-2019, was aimed to explore the potential use of coal FA in soil along  with fertilizer and vermicompost (VC). The experiment comprised of eight  treatments i.e. different doses of FA (10, 20, 30, 40 and 50 t ha-1) along with 2 t VC ha-1 and fertilizer (basal dose of NPK), control (no amendment),  fertilizer only and VC only. The study revealed that treatment 20 t ha-1 FA  + VC + fertilizer had maximum enzymatic activity between 45th to 60th day. Metagenomic study of this treatment showed Betaproteobacteria (22%), Halophaga(17%), Acidimicrobiia (10%) and Nitrosptra (10%) as the most  abundant bacterial class, while order Bacillales (22%), Ardenscatenales(16%), Deinococcales (8%) and Actinomycetales (4%). The most abundant orders were Clostridiales (22%), Chroococcales (17%),(10%), and Gemmatimonadales (8%). At family level most abundant were  Clostridiaceae (25%), Xenococcaceae (12%) and Pseudoanabaenaceae (8%).  The study reveals the reduction in hazardous impact of fly-ash on soil and  thereby signifies its potential use to improve the crop yield and quality.
Keywords: Enzyme; fly ash; metagenomic; microbes; vermicompost